Fracture toughness of matrix cracked FRC and FGC beams using equivalent TPFM - A.A. Elakhras; M.H. Seleem; H.E.M. Sallam (Fracture and Structural Integrity)
In the present work, the fracture toughness (KIC) of full-depth (FD) fiber-reinforced concrete (FRC) and layered functionally graded concrete (FGC) matrix cracked (MC) beams has been determined by the equivalent relationships of the two-parameter fracture model (ETPFM). Forty-eight MC-FGC and MC-FD FRC beam specimens with span-depth ratios (L/d) equal 4, 5, and 6 were tested under the 3PB configuration. The MC length-depth ratio (ao/d) remained constant equal to one-third. All FRC beams have the same hooked-end steel fibers volume fraction of 1%. The FGC beams are composed of three equal layers, i.e., FRC in the bottom layer at the tension side, normal strength concrete (NSC) at the middle layer, and high strength concrete at the upper layer in the compression side. The results showed that the predicted values of KICobtained from ETPFM are considered appropriate according to the maximum size of the non-damaged defect concept. The crack mouth opening displacement estimated from ETPFM showed acceptable values close to the present experimental results. The KIC values calculated within the presence of fibers in front of and through the MC for FRC beam specimens having 1% SFs is more than twice the value of NSC.